Kinerja kalium metavanadat sebagai inhibitor korosi baja karbon rendah dalam lingkungan klorida dan sulfida - Isdiriayani Nurdin; R Asri Pratiwi; Aditya Farhan A; Fikri Anggara P; Rennie Sari (Jurnal Teknik Kimia Indonesia, 2008)
Inhibitor addition is one of the common corrosion control methods. Potassium metavanadate (KVO3) is the common corrosion inhibitor for Benfield solution in CO2 absorber. Former research shows that KVO3 is also able to inhibit the corrosion in seawater containing Sulphate Reducing Bacteria (SRB) due to its capacity as biocide. Chloride and Sulfide are common corrosive ions found in process fluids in industries. Therefore, this research is carried out to study the performance of KVO3 as a corrosion inhibitor for low- carbon steel in chloride and sulfide contaminated environment. The objective of this research was achieved by measuring low-carbon steel corrosion rate in various concentrations of contaminants. The corrosion rate was measured by Tafel method. The corrosion inhibition mechanisms were studied using cyclic voltammetry method. Meanwhile the corrosion products were identified by X - ray diffraction spectrometry (XRD). This research results that KVO3 is an effective corrosion inhibitor in chloride environment when the chloride concentration ranges between 20 g/L and 30 g/L. In this range of concentration, KVO3 performs more than 99% efficiency. While in sulfide environment, KVO3 is an ineffective corrosion inhibitor. On the other hand, the addition of KVO3 reduces the corrosion rate of carbon steel in seawater containing sulfide, although its performance does not meet the effective inhibitor criteria. Higher concentration of sulfide results the higher inhibition efficiency of KVO3.Keywords: Potassium metavanadate, low - carbon steel, corrosion inhibitor AbstrakPenambahan inhibitor merupakan salah satu metode pengendalian korosi. Kalium metavanadat (KVO3) sering digunakan sebagai inhibitor korosi pada absorber CO2 yang menggunakan larutan Benfield. Hasil penelitian sebelumnya menunjukkan bahwa KVO3 mampu menginhibisi korosi baja karbon rendah dalam air laut yang mengandung bakteri pereduksi sulfat (SRB) dengan bertindak sebagai biosida. Klorida dan sulfida merupakan ion-ion korosif yang umum ditemui dalam fluida proses di industri. Penelitian ini dilakukan untuk mempelajari kinerja KVO3 sebagai inhibitor korosi baja karbon rendah dalam lingkungan akuatik yang terkontaminasi klorida, ataupun sulfida. Untuk mencapai tujuan tersebut dilakukan pengukuran laju korosi baja karbon rendah dengan jenis dan konsentrasi kontaminan bervariasi. Pengukuran laju korosi dilakukan dengan metode Tafel. Mekanisme inhibisi diprediksi dengan metode voltametri siklik. Sedangkan produk korosi diidentifikasi dengan menggunakan spektrometri difraksi sinar X (XRD). Dari penelitian ini, diperoleh hasil bahwa KVO3 efektif sebagai inhibitor korosi baja karbon rendah pada lingkungan klorida berkonsentrasi antara 20 g/L hingga 30 g/L dengan efisiensi di atas 99%. Pada lingkungan sulfida, KVO3 kurang efektif menginhibisi korosi baja karbon rendah. Sedangkan pada air laut sintetik yang mengandung sulfida, walaupun belum termasuk kategori inhibitor efektif, namun KVO3 dapat menurunkan laju korosi baja karbon dengan efisiensi inhibisi yang meningkat seiring dengan kenaikan konsentrasi sulfida.Kata kunci: kalium metavanadat, baja karbon rendah, inhibitor korosi